Material Selection and Analysis of Torsional Rigidity in Formula Student SAE regulation - Dionisius, Felix; Arif, Imam Nur; Endramawan, Tito; Sifa, Agus; Badruzzaman, Badruzzaman (INVOTEK: Jurnal Inovasi Vokasional dan Teknologi, 2022)
The advancement of automotive technology is rapid in this era, as evidenced by the existence of autopilot vehicles that have been developed by a scientist. This progress is balanced with the knowledge that continues to develop in the world of education. Many prestigious automotive competitions are held to be a venue for student creativity and research in developing automotive technology, one of which is the Formula Student SAE. This is the background of a study to develop an engineered electric vehicle chassis, especially in Formula Student. This study aims to produce a chassis design that has torsional rigidity based on the selection of materials that have stiffness, strength, lightweight, and optimization of material cost. The structure of the vehicle was designed following Formula Student SAE regulations. To select material, initial screening was used by the Ashby method which produce 4 material types. Optimum of selecting the material used the Simple Additive Weighting (SAW) method. Meanwhile, chassis with material selected was analyzed by using Solidworks Simulation Education software. The results of this study produced Aluminum Alloys 7075-T6 material and torsional rigidity value of 552.65 x 103 Nmm/degree of chassis, which could achieve the minimum torsional rigidity value set at 500 x 103 Nmm/degree.